Rheumatic Heart Disease in the Developing World - Jacobson, Anne (MD Conference Express, 2008)
Although the latter part of the last century saw a dramatic decline in the incidence of rheumatic heart disease (RHD) in the developed world, it remains a major cause of cardiovascular morbidity and mortality in developing countries. Worldwide, more than 15 million individuals have RHD. Socioeconomic gradient remains the most important barrier among these countries or within a developing country with regard to both susceptibility to RHD and availability of cardiovascular care.